STRATEGIC DIRECTIONS OF STRUCTURAL AND INSTITUTIONAL TRANSFORMATION OF THE REGIONAL LABOR MARKET UNDER CONDITIONS OF INSTABILITY - LEVYTSKA, Olha; HRES, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article focuses on the strategic directions of structural changes and institutional reforms in the regional labor market under conditions of instability. The purpose of the study is to substantiate the key tasks and priorities of labor market modernization in the Lviv region, taking into account the challenges of war, the displacement of the working population, and the urgent need for economic recovery. The research emphasizes the multidimensional nature of structural transformations, which require not only economic adaptation but also institutional flexibility and social resilience. The essential characteristics of structural imbalances and institutional problems in regional employment are summarized, including the mismatch between qualifications and labor demand, unequal territorial development, limited access to quality jobs, and insufficient professional retraining opportunities.It is established that the crucial factors in shaping a balanced labor market include ensuring the correspondence between labor demand and supply, overcoming disparities in the development of urban and rural areas, enhancing the population’s professional skills, improving social dialogue, modernizing workplaces, and implementing innovations in labor organization. Particular attention is given to the role of educational institutions and local authorities in fostering workforce adaptability and supporting entrepreneurship as a tool for job creation.The article highlights the importance of digitalization and remote employment forms, which can help mitigate regional disparities and integrate internally displaced persons into productive activity. It is proved that the implementation of these strategic priorities will contribute to strengthening human resources, increasing the competitiveness of the regional economy, reducing unemployment, and forming a sustainable development model in the post-war recovery period. The conclusions underline that successful labor market modernization requires coordinated efforts of the state, business, and civil society to ensure inclusive, innovative, and socially oriented growth.
Keywords: regional labor market; structural changes; institutional reforms; strategic priorities; balanced development; employment; labor potential